Hubungan antara Stroke Iskemik dengan Gangguan Fungsi Kognitif di RSUD Dr. Moewardi - Mustikawati, Ade Putri; , dr. Ani Rusnani Fibriani, Sp.S; , dr. Nining Lestari (2016)
Background: Ischemic stroke is a disorder of brain function that occur suddenly and caused a blockage in the blood vessel (thromboembolic), resulting in area under experienced ischemic blockage. The most common symptoms of a stroke is sudden weakness of one side of the body on the face, arms, and legs. Other symptoms such as impaired cognitive function. In previous studies of acute ischemic stroke to impaired cognitive function, namely a decline in cognitive function in patients with ischemic stroke . Objective: This study aims to determine the relationship between ischemic stroke with impaired cognitive function. Methods: The design study is observational method with cross sectional study design. The population in this study were stroke patients neurological polyclinic Hospital Dr. Moewardi and for controls taken from patients admitted Dr. Moewardi Hospital through the clinic diagnosed nerve and not a stroke. The sample in this study were all patients with a diagnosis based on CT - scan as ischemic stroke. Large samples of 56 patients with a comparison of cases and controls. The sampling technique is purposive sampling. Data were analyzed using Chi-square using SPSS version 21.0 for Windows. Result: There is a statistically significant relationship ischemic stroke with impaired cognitive function. Respondents in the case group included the category of normal cognitive function by 25 respondents (44.6 %), whereas impaired cognitive function as much as 31 respondents (55.4 %). While the control group of 56 respondents, which decreased cognitive impairment by 2 respondents. The results of Chi-square test of hypothesis obtained significancy 0.000 where p < 0.05. Conclusion: There is a relationship between ischemic stroke with impaired cognitive function in Dr. Moewardi Hospital of Surakarta statistically significant.